Drought tolerance screening under controlled conditions predicts ranking of water-limited yield of field-grown soybean genotypes - Pardo, E. M. (2015)
Drought is a major limitation to crop yields worldwide. Screening for soybean yield under water deficit is often a bottleneck in breeding programmes. We assessed the validity of a standardized drought tolerance screening method to predict water-limited field performance of soybean in NW Argentina. First, to determine the phenological period when yield of glasshouse-grown plants was more sensitive to water deficit, we applied treatments during 21 days in V7, R3 or R5 stages, being the period from R5 to R6 the most critical for yield. Afterwards, two glasshouse experiments were carried out to quantify the tolerance of either eight or four genotypes, respectively, by applying a controlled water deficit of constant intensity during the critical period. Finally, yield data obtained in field trials in Argentina across several locations and seasons classified according to rainfall were analysed. Drought Susceptibility Index was calculated for each experiment and for field data, and rankings of tolerance were similar in all cases. This standardized method, which can be automated for high-throughput phenotyping, could represent a useful tool in breeding programmes for identifying soybean cultivars with improved performance under drought conditions.